Models, systems, and descriptions - Prinz, Andreas; Engebretsen, Martin; Gjøsæter, Terje; Møller-Pedersen, Birger; Xanthopoulou, Themis Dimitra (Frontiers in Computer Science, 2023)
There are many different notions of models in different areas of science that are often not aligned, making it difficult to discuss them across disciplines. In this paper, we look at the differences between physical models and mental models as well as the difference between static and dynamic models. Semiotics provides a philosophical underpinning by explaining meaning-making. This allows for identifying a common ground between models in different areas. We use examples from natural sciences and linguistics to illustrate different approaches and concepts and to find commonalities. This paper distinguishes between systems, models, and descriptions of models. This distinction allows us to understand the commonalities of mental and physical models in different areas.